Quality of Life After Translabyrinthine Vestibular Schwannoma Resection—Reliability of the German PANQOL Questionnaire. Issue 6 (July 2018) - Glaas, Marcel Fabian; Schäfer, Ralf; Jansen, Philipp; Franz, Matthias; Stenin, Igor; Klenzner, Thomas; Schipper, Jörg; Eysel-Gosepath, Katrin; Kristin, Julia
Abstract : Objective: To quantify the postoperative quality of life (QOL) of patients after translabyrinthine surgery for vestibular schwannoma (VS) using the German version of the Penn acoustic neuroma quality-of-life questionnaire (PANQOL) in a university hospital. Methods: The PANQOL questionnaire was administered to 72 patients who were treated in our department with translabyrinthine surgery for VS between January 2007 and January 2017. Descriptive evaluations of results were performed in addition to analyses of the reliability and convergent validity of the results and a subgroup analysis. Results: For the first time, QOL was measured in German-speaking VS patients after translabyrinthine surgery. Cronbach's alpha for internal consistency and Guttman's split half, used as measures of reliability, showed values between 0.39 and 0.92 (raw alpha) and 0.58 and 0.98 (Lambda 4), respectively. Descriptive Statistics: The mean total PANQOL score of patients after translabyrinthine VS resection was 61.96. The domain "hearing" had the lowest score (50.87), while "facial dysfunction" had the highest score (74.88). Subgroup analysis showed that neither preoperative tumor size nor elapsed time postoperatively significantly influenced QOL outcomes. Conclusions: Depending on the different domains the German PANQOL questionnaire showed poor to good internal consistency, reliability, and convergent validity. Moreover, some VS patients suffer from reduced QOL for a long time after the translabyrinthine procedure, thus psycho-oncological care should be recommended in these cases.